2019
DOI: 10.3390/children6080091
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Processes Underlying Reading Improvement during a Rhythm-Based Intervention. A Small-Scale Investigation of Italian Children with Dyslexia

Abstract: Music and rhythm-based training programs to improve reading are a novel approach to treatment of developmental dyslexia and have attracted the attention of trainers and researchers. Experimental studies demonstrating poor basic auditory processing abilities in individuals with dyslexia suggest they should be effective. On this basis, the efficacy of a novel rhythm-based intervention, Rhythmic Reading Training (RRT), was recently investigated and found to improve reading skills in Italian children with dyslexia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Furthermore, RRT's efficacy was found to be comparable to that of a traditional reading intervention involving homework [49] and to that of a novel intervention involving visuo-spatial and attentional stimulations [50], with specific larger effects of RRT on pseudo-word reading speed. Finally, significant improvements following RRT were maintained three months after completion of the intervention [46]. Such evidence confirms the feasibility and efficacy of the RRT method for reading training in DD.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Furthermore, RRT's efficacy was found to be comparable to that of a traditional reading intervention involving homework [49] and to that of a novel intervention involving visuo-spatial and attentional stimulations [50], with specific larger effects of RRT on pseudo-word reading speed. Finally, significant improvements following RRT were maintained three months after completion of the intervention [46]. Such evidence confirms the feasibility and efficacy of the RRT method for reading training in DD.…”
Section: Introductionsupporting
confidence: 67%
“…Besides the small sample size, one of the limitations of the present study was the lack of follow-up measures, which would assess the long-term effects of the intervention. However, a previous study on RRT showed that reading gains after intervention lasted for three months [46]. Although we expect that such results should be replicated in both inpresence and telerehabilitation settings, future investigations may compare the long-term effects of RRT in different administration conditions.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…A test-training-retest study showed the efficacy of RRT intervention on reading abilities of 14 junior high school students with DD, compared to a matched control group that received no intervention (Bonacina et al, 2015). Other test-training-retest small scale studies supported RRT efficacy in primary and junior high-school Italian students with DD, under different conditions (Cancer and Antonietti, 2017;Cancer et al, 2019).…”
Section: Rhythmic Reading Training (Rrt)mentioning
confidence: 99%
“…To date, there is a lack of studies utilizing real music rhythm to measure the rhythm induction for children with dyslexia. Even though the effects of musical training has been examined in individuals with reading problems (Cancer et al, 2019), but the rhythm induction of brain response in real musical beats for dyslexic children is still not investigated.…”
Section: Introductionmentioning
confidence: 99%